2022
DOI: 10.1002/ctm2.848
|View full text |Cite
|
Sign up to set email alerts
|

YTHDF2 promotes intrahepatic cholangiocarcinoma progression and desensitises cisplatin treatment by increasing CDKN1B mRNA degradation

Abstract: Background Intrahepatic cholangiocarcinoma (ICC) is an aggressive cancer with exceedingly poor prognosis, and chemoresistance is a huge challenge for treatment. N6‐methyladenosine (m 6 A) modification plays an important role in the progression and chemoresistance of cancers. We aimed to investigate the oncogenic function and therapeutic significance of the m 6 A binding protein, YTH domain family 2 (YTHDF2), in ICC progression and cisplatin‐bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…Cisplatin promotes tumor cell apoptosis by forming an adduct with the DNA of tumor cells, thereby achieving its anti-tumor effect [ 32 ]. Many studies have confirmed that the decrease in cell cycle arrest is the key factor in tumor cisplatin resistance [ 33 , 34 , 35 ]. We found that the overexpression of miR - 660 decreased the cell proliferation capacity and increased the cell apoptosis rate and cell cycle arrest in cisplatin-treated A549/CDDP and CALU-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin promotes tumor cell apoptosis by forming an adduct with the DNA of tumor cells, thereby achieving its anti-tumor effect [ 32 ]. Many studies have confirmed that the decrease in cell cycle arrest is the key factor in tumor cisplatin resistance [ 33 , 34 , 35 ]. We found that the overexpression of miR - 660 decreased the cell proliferation capacity and increased the cell apoptosis rate and cell cycle arrest in cisplatin-treated A549/CDDP and CALU-3 cells.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, YTHDF1 and YTHDF2 facilitate the advancement of intrahepatic cholangiocarcinoma (ICC) through increasing EGFR mRNA translation and IFIT2 mRNA decay, respectively ( 188 , 189 ). Meanwhile, YTHDF2 silencing restrains ICC resistance to the exposure of cisplatin by reversing the degradation of cyclin-dependent kinase inhibitor 1B (CDKN1B) mRNA ( 190 ).…”
Section: The Role Of the Ythdf Family In Cancersmentioning
confidence: 99%
“…ALKBH5-mediated m 6 A demethylation stabilizes CASC8 transcription, ultimately leading to cisplatin resistance in ESCC [120]. Furthermore, YTHDF2 increased CDKN1B mRNA degradation in an m 6 A-dependent manner, which promoted intrahepatic cholangiocarcinoma (ICC) progression and reduced sensitivity to cisplatin treatment [121]. m 6 A modifications also play an integral part in tamoxifen resistance, a classical chemotherapeutic agent in breast cancer treatment [122].…”
Section: Induced Specific Drug Resistancementioning
confidence: 99%